Equine Chorionic Gonadotropin as an Effective FSH Replacement for In Vitro Ovine Follicle and Oocyte Development - Chiara Di Berardino (MDPI AG, 2021)
The use of assisted reproductive technologies (ART) still requires strategies through which to maximize individual fertility chances. In vitro folliculogenesis (ivF) may represent a valid option to convey the large source of immature oocytes in ART. Several efforts have been made to set up ivF cultural protocols in medium-sized mammals, starting with the identification of the most suitable gonadotropic stimulus. In this study, Equine Chorionic Gonadotropin (eCG) is proposed as an alternative to Follicle Stimulating Hormone (FSH) based on its long superovulation use, trans-species validation, long half-life, and low costs. The use of 3D ivF on single-ovine preantral (PA) follicles allowed us to compare the hormonal effects and to validate their influence under two different cultural conditions. The use of eCG helped to stimulate the in vitro growth of ovine PA follicles by maximizing its influence under FBS-free medium. Higher performance of follicular growth, antrum formation, steroidogenic activity and gap junction marker expression were recorded. In addition, eCG, promoted a positive effect on the germinal compartment, leading to a higher incidence of meiotic competent oocytes. These findings should help to widen the use of eCG to ivF as a valid and largely available hormonal support enabling a synchronized in vitro follicle and oocyte development.